Grammar the easy way - Mulvey, Dan (Barron's, 2002)
Reviews basic grammar, including parts of speech, sentence structure, and subject-verb agreement; provides a manual of usage, instruction on writing paragraphs and research papers, and how to develop one's own style; and includes exercises and a test.